Efeitos da intervenção fisioterapêutica na diástase dos retos abdominais em gestantes - Cabral, Alana Leandro (2024)
Introduction: Diastasis recti abdominis (DRA), common in pregnant women, is characterized by an increase in the inter-rectus distance (IRD), generally measured by ultrasound (US). Exercises that focus on activating the transverse abdominis (TrA) muscle are often recommended to decrease DIR, while rectus abdominis exercises are avoided. However, the effectiveness of these recommendations is not proven due to a lack of scientific evidence. Furthermore, there is a gap in knowledge about these exercises in pregnant women. To fill this gap, two studies were carried out. Objectives: Article 1: To evaluate intra- and inter-rater reliability, and calculate the minimum detectable difference (MDC) and standard error of IRD measurements in nulliparous women, using US. Article 2: Compare exercises that activate the TrA and the rectus abdominis muscles with exercises without specific activation of these muscles in the IRD of pregnant women, and verify their repercussions on the dysfunctions of the pelvic floor muscles (PFM). Material and Methods: Article 1: 21 nulliparous women underwent IRD measurement, in two different positions (rest and trunk flexion) and in two different regions (supraumbilical and infraumbilical), by two experienced radiologists at two different times. Article 2: 63 pregnant women were divided into 3 intervention groups: Drawing-in (exercises with TrA activation); Abdominal crunch (exercises with activation of the rectus abdominis); Control (exercises without specific activation of the abdominal muscles). The intervention lasted 12 weeks, with initial assessments and at the end of this period, through measuring the DIR (in the same locations and positions as nulliparous women) and the Pelvic Floor Discomfort Questionnaire (PFBQ). Results: Article 1: DIR measurements showed high intra-rater reliability for all variables, with ICC above 0.80. Inter-rater reliability was moderate in the supraumbilical region in both positions, with ICC: rest: 0.720 (0.492; 0.857) and flexion 0.760 (0.447; 0.891). However, reliability was low in the infraumbilical region in both positions, rest: 0.276 (-0.038, 0.558) and flexion 0.257 (-0.109, 0.564). MDC values varied between 0.22 and 0.50 cm. Article 2: For the DIR variable, no group-time interaction was demonstrated when evaluated at supraumbilical rest [F(2,60) = 0.30; p= 0.742] and infraumbilical [F(1,40) = 0.107; p= 0.899]. This also occurred in the flexion position in the supraumbilical region [F(2,60) = 1.03; p= 0.362] and infraumbilical [F(2,60) = 1.23; p= 0.301]. There were no differences between the groups in any of the variables. For the PFBQ, the p values suggest that there was no group-time interaction [F(2,60) = 2.14; p= 0.126], nor was there any effect of time or group. Conclusion: Article 1: US is a reliable method for measuring IRD in the supraumbilical region. Article 2: Specific abdominal exercises do not induce changes in the size of the IRD in pregnant women. Furthermore, they do not cause changes in the symptoms of PFM dysfunctions.